2021
DOI: 10.1109/tmi.2021.3057635
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable Multimodal Fusion Networks Reveal Mechanisms of Brain Cognition

Abstract: Multimodal fusion benefits disease diagnosis by providing a more comprehensive perspective. Developing algorithms is challenging due to data heterogeneity and the complex withinand between-modality associations. Deep-network-based datafusion models have been developed to capture the complex associations and the performance in diagnosis has been improved accordingly. Moving beyond diagnosis prediction, evaluation of disease mechanisms is critically important for biomedical research. Deep-network-based data-fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…When the attention mechanism is introduced to distribute weight, formula ( 1 ) can be used to distribute weight [ 18 ]: where L represents the number of keywords and Similarity ( ) means similarity calculation function, which usually includes the following three functions: where W represents the learnable parameter and d represents the dimension of keyword and weight value.…”
Section: Basic Methodsmentioning
confidence: 99%
“…When the attention mechanism is introduced to distribute weight, formula ( 1 ) can be used to distribute weight [ 18 ]: where L represents the number of keywords and Similarity ( ) means similarity calculation function, which usually includes the following three functions: where W represents the learnable parameter and d represents the dimension of keyword and weight value.…”
Section: Basic Methodsmentioning
confidence: 99%
“…Various studies have confirmed that a combination of multi-modal data can improve the performance of predictive models [41,42,31,43,27,44]. Most of these studies concatenated the feature vectors into a single vector for prediction or classification.…”
Section: Multi-modal Data Fusionmentioning
confidence: 99%
“…Neuroimaging studies [35], [36] have found that visual pathways across in several brain regions are responsible for visual information processing. Besides, paper [37] has indicated that the complicated relationships among different EEG electrodes are significant for recognition tasks. Therefore, the characteristics of spatial connections in the brain needs to be explored when designing networks for EEG classification.…”
Section: Introductionmentioning
confidence: 99%